Ceramide on the road to insulin resistance and immunometabolic disorders in transition dairy cows: driver or passenger? - Zhao, Yuchao; Zhao, Huiying; Li, Liuxue; Yu, Shiqing; Liu, Ming; Jiang, Linshu (Frontiers in Immunology, 2024)
Dairy cows must undergo profound metabolic and endocrine adaptations during their transition period to meet the nutrient requirements of the developing fetus, parturition, and the onset of lactation. Insulin resistance in extrahepatic tissues is a critical component of homeorhetic adaptations in periparturient dairy cows. However, due to increased energy demands at calving that are not followed by a concomitant increase in dry matter intake, body stores are mobilized, and the risk of metabolic disorders dramatically increases. Sphingolipid ceramides involved in multiple vital biological processes, such as proliferation, differentiation, apoptosis, and inflammation. Three typical pathways generate ceramide, and many factors contribute to its production as part of the cell’s stress response. Based on lipidomic profiling, there has generally been an association between increased ceramide content and various disease outcomes in rodents. Emerging evidence shows that ceramides might play crucial roles in the adaptive metabolic alterations accompanying the initiation of lactation in dairy cows. A series of studies also revealed a negative association between circulating ceramides and systemic insulin sensitivity in dairy cows experiencing severe negative energy balance. Whether ceramide acts as a driver or passenger in the metabolic stress of periparturient dairy cows is an unknown but exciting topic. In the present review, we discuss the potential roles of ceramides in various metabolic dysfunctions and the impacts of their perturbations. We also discuss how this novel class of bioactive sphingolipids has drawn interest in extrahepatic tissue insulin resistance and immunometabolic disorders in transition dairy cows. We also discuss the possible use of ceramide as a new biomarker for predicting metabolic diseases in cows and highlight the remaining problems.